A review of technical and regulatory limits for hydrogen blending in natural gas pipelines. (15th February 2023) - Erdener, Burcin Cakir; Sergi, Brian; Guerra, Omar J.; Lazaro Chueca, Aurelio; Pambour, Kwabena; Brancucci, Carlo; Hodge, Bri-Mathias
Abstract: There is rising interest globally in the use of hydrogen for the provision of electricity or heat to industry, transport, and other applications in low-carbon energy systems. While there is attention to build out dedicated hydrogen infrastructure in the long-term, blending hydrogen into the existing natural gas pipeline network is also thought to be a promising strategy for incorporating hydrogen in the near-term. However, hydrogen injection into the existing gas grid poses additional challenges and considerations related to the ability of current gas infrastructure to operate with blended hydrogen levels. This review paper focuses on analyzing the current understanding of how much hydrogen can be integrated into the gas grid from an operational perspective and identifies areas where more research is needed. The review discusses the technical limits in hydrogen blending for both transmission and distribution networks; facilities in both systems are analyzed with respect to critical operational parameters, such as decrease in energy density, increased flow speed and pressure losses. Safety related challenges such as, embrittlement, leakage and combustion are also discussed. The review also summarizes current regulatory limits to hydrogen blending in different countries, including ongoing or proposed pilot hydrogen blending projects. Highlights: Hydrogen could help to decarbonize challenging to decarbonize sectors. Hydrogen blending into the existing gas networks could be advantageous. Hydrogen blending impacts on gas network components require a better understanding.